Thermal Adaptation and Comfort Zones in Urban Semi-Outdoor Environments - Nakano, Junta; Tanabe, Shin-ichi (Frontiers in Built Environment, 2020)
In this work, thermal adaptation characteristics and thermal comfort zones were investigated in urban semi-outdoor environments in Tokyo. Four spaces with different levels of environmental control, i.e., heating, ventilation, and air conditioning (HVAC) spaces and non-HVAC spaces, were selected for the seasonal field surveys lasting over a period of 80 days. The survey consisted of the thermal environment measurement, questionnaire survey, and observation of occupancy conditions. The occupants were adapting themselves to fit within a certain range of standard effective temperature (SET∗). Clothing adjustment was the principal form of behavioral adaptation. The dominant factor affecting the clothing adjustment was the daily mean outdoor temperature, and not the immediate environment, in both the non-HVAC and the HVAC spaces. The total number of occupants and the mean occupancy period of the day had a strong linear relationship with the daily mean air temperature of the occupied zone in the non-HVAC spaces. No correlation was found between the thermal environment and the occupancy conditions in the HVAC spaces. Adaptive thermal comfort zones, not comfort temperatures, were derived directly from the subjective votes. The comfort zone in SET∗ was found to be 23–28°C for the predicted percentage of dissatisfied (PPD), 18–29°C for HVAC spaces, and 14–32°C for non-HVAC spaces. Occupants in semi-outdoor environments were tolerant to their thermal environment two to three times wider in range than the one predicted by the PPD. These findings are expected to be useful in the design and assessment of urban semi-outdoor environments.